Host-Microbiome Interaction in Lung Cancer - Dong, Qiang; Chen, Eric S.; Zhao, Chen; Jin, Chengcheng (Frontiers in Immunology, 2021)
Commensal microbiota has emerged as an important biomarker and regulator of both tumorigenesis and response to cancer therapy. Yet our current knowledge about microbiota in cancer has been largely limited to intestinal microbiota. As a mucosal organ harboring one of the largest surface areas in the body, the lung is exposed to a variety of microbes through inhalation and micro-aspiration, and it is colonized by a diverse bacterial community in both physiological and pathological conditions. Importantly, increasing evidence has linked lung microbiome to cancer development. Studies in lung cancer patients and mouse models have revealed tumor-associated dysregulation of the local microbiome in the lung, which in turn impacts cancer progression by shaping the tumor microenvironment and modulating the activity of tumor-infiltrating immune cells. These findings not only provide novel mechanistic insight to the biology of lung cancer, but they also shed light on new therapeutic targets and strategies for lung cancer prevention and treatment. The goal of this review is to summarize the key findings in this new field, and to discuss the remaining questions and future directions.